Discrepant molecular and clinical diagnoses in Beckwith-Wiedemann and Silver-Russell syndromes. (4th March 2019) - Mackay, Deborah J.G.; Bliek, Jet; Lombardi, Maria Paola; Russo, Silvia; Calzari, Luciano; Guzzetti, Sara; Izzi, Claudia; Selicorni, Angelo; Melis, Daniela; Temple, Karen; Maher, Eamonn; Brioude, Frédéric; et al.
Abstract: Beckwith-Wiedemann syndrome (BWS) and Silver-Russell syndrome (SRS) are two imprinting disorders associated with opposite molecular alterations in the 11p15.5 imprinting centres. Their clinical diagnosis is confirmed by molecular testing in 50–70% of patients. The authors from different reference centres for BWS and SRS have identified single patients with unexpected and even contradictory molecular findings in respect to the clinical diagnosis. These patients clinically do not fit the characteristic phenotypes of SRS or BWS, but illustrate their clinical heterogeneity. Thus, comprehensive molecular testing is essential for accurate diagnosis and appropriate management, to avoid premature clinical diagnosis and anxiety for the families.